Novel ultrabright luminescent copper nanoclusters and application in light-emitting devices. Issue 77 (8th September 2021) - Huang, Qiu-Qin; Hu, Mei-Yue; Li, Yan-Li; Chen, Nan-Nan; Li, Yi; Wei, Qiao-Hua; Fu, FengFu
Abstract : Ultra-small tri/tetra-nuclear copper nanoclusters (Cu3 /Cu4 ) exhibit ultrabright phosphorescence emission ( Ф em  = 71.8 and 63.5%). Cu3  is firstly applied as a single component phosphor for white light-emitting diodes with favourable characteristics. Abstract : Two newly synthesized ultra-small copper nanoclusters, [Cu3 (μ3 -H)(μ2 -dppy)4 ](ClO4 )2 (1) and [Cu4 (μ4 -H)(μ2 -dppy)4 (μ2 -Cl)2 ](ClO4 ) (2) (dppy = diphenyl-2-pyridylphosphine), have been shown to exhibit ultrabright yellow and yellow-green room-temperature phosphorescence (RTP) emission, with high quantum yields of 71.8% and 63.5%, respectively. Therefore, nanocluster 1 has been applied for the first time as a single component phosphor for yellow and white light-emitting diodes (LEDs) with favourable characteristics.